Pengaruh Pemanfaatan Kecerdasan Buatan dan Chatbot Terhadap Pengalaman Pelanggan Tokopedia pada Mahasiswa FEB Universitas Negeri Gorontalo - Riska Bilondatu; Rizan Machmud; Syamsul B. Biki (Transbahasa, 2026)
This study aims to analyze the effect of Artificial Intelligence (AI) and Chatbot utilization on Customer Experience among Tokopedia users. The research method used a quantitative approach with a sample of 100 respondents from the Faculty of Economics and Business, Class of 2022, UNG, selected through purposive sampling. Data analysis was performed using multiple linear regression. The results show that partially, AI has a positive and significant effect on Customer Experience (t-count 3.193 > 1.984). Similarly, the Chatbot variable has a significant effect (t-count 5.357 > 1.984). Simultaneously, both variables have a significant effect with an F- count of 69.866 > 3.09. The R² value of 0.590 indicates a 59.0% contribution to Customer Experience. The integration of artificial intelligence (AI) and chatbots has made a positive contribution to improving service efficiency. Nevertheless, inconsistencies in previous findings (research gap) remain evident in the existing literature. In conclusion, optimizing AI and chatbot technology is a crucial factor in enhancing the quality of digital transaction experiences for students.